A Rare Cause of Secondary Amyloidosis: Common Variable Immunodeficiency Disease - Ali Kemal Kadiroğlu; Yaşar Yıldırım; Zülfükar Yılmaz; Hasan Kayabaşı; Yahya Avcı; M. Serdar Yıldırım; M. Emin Yılmaz (Case Reports in Nephrology)
The common variable immunodeficiency disease (CVID) is the most common symptomatic primary antibody deficiency. It is the most frequently observed cause of panhypogammaglobulinemia in adults. Here, we present a case of systemic amyloidosis that developed secondary to the common variable immunodeficiency disease causing recurrent infections in a young female patient. A 24-year-old female patient, who was under treatment at the gynecology and obstetrics clinic for pelvic inflammatory disease, was referred to our clinic when she was observed to have swellings in her legs, hands, and face. She had proteinuria at a rate of 3.5 gr/day, and her serum albumin was 1.5 gr/dl. The levels of immunoglobulins are IgG: 138 mg/dl, IgA: 22,6 mg/dl, and IgM: 16,8 mg/dl. The renal USG revealed that the kidneys were observed to be enlarged. Since the patient had recurrent infections, hypogammaglobulinemia, nephrotic range proteinuria, and enlarged kidneys in the renal USG, she was thought to have type AA amyloidosis and therefore underwent a renal biopsy. The kidney biopsy revealed amyloid (+). So the patient was diagnosed with AA type of amyloidosis secondary to common variable immunodeficiency disease. A treatment regimen (an ACE inhibitor and a statin) with monthly administration of intravenous immunoglobulin was started.